Association of Weaning Practice with Severe Acute Malnutrition in Children Presenting to the Nutritional Rehabilitation Unit - Hussain, Saddam; Muhammad, Amir; Khan, Muhammad; Shah, Syed Habib (Biological and Clinical Sciences Research Journal, 2025)
Appropriate timing of complementary feeding plays a critical role in child growth and nutritional status. Delayed or inappropriate weaning practices may contribute to severe acute malnutrition (SAM), a major cause of morbidity and mortality among children under two years of age, particularly in low-resource settings. Objective: To determine the frequency of severe acute malnutrition in children with early and late weaning practices presenting to a Nutritional Rehabilitation Unit. Methods: This cross-sectional study included 159 children aged 2–24 months presenting to a Nutritional Rehabilitation Unit. Early weaning was defined as the introduction of complementary foods before six months of age, while late weaning was defined as the introduction after six months from 21-12-2024 to 21-04-2025. Children with congenital anomalies, genetic disorders, neurological impairments, and those receiving treatment for severe acute malnutrition within the previous three months were excluded. All children were assessed for SAM based on standard anthropometric criteria. Data were analyzed using SPSS version 26. Associations were evaluated using appropriate statistical tests, with a p-value <0.05 considered statistically significant. Results: The mean age of the children was 15.09 ± 5.18 months, and the mean weight was 9.41 ± 1.10 kg. Late weaning was observed in 110 children (69.2%), while early weaning was reported in 49 children (30.8%). The overall frequency of severe acute malnutrition was 46.5% (n=74). Among children with SAM, 77.0% (n=57) had a history of late weaning, whereas 23.0% (n=17) had early weaning (p=0.04). Severe acute malnutrition was significantly associated with lower weight category (p = 0.002), rural residence (p = 0.002), and lower parental education level (p = 0.01). Conclusion: Late weaning practice was significantly associated with a higher frequency of severe acute malnutrition. Additionally, lower weight category, rural residence, and lower parental education were significant risk factors. Strengthening caregiver education regarding appropriate complementary feeding practices may help reduce the burden of severe acute malnutrition.